Analysis of Psychological Factors and Strategies for Building Religious Character in Overcoming Deviant Behavior among Sixth Grade Students at SDIT Darunnajah - Hanif Faddillah; Widiya Yul (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aims to analyze psychological factors contributing to deviant behavior among sixth-grade elementary students and to examine religious character development strategies implemented by schools to address such behavior, with the goal of identifying effective and sustainable approaches for guiding students toward positive behavioral and character development. The research employed a qualitative case study design using purposive sampling, with data collected through in-depth interviews, direct observations, and documentation studies involving school leaders, teachers, students, and parents, and analyzed using the Miles and Huberman model consisting of data reduction, data display, and conclusion verification procedures. The findings reveal that students’ deviant behaviors are influenced by emotional pressure, family relationship issues, the need for peer recognition, weak emotional regulation, and exposure to digital media, while strategies such as empathetic communication, teacher role modeling, structured worship habituation, personal mentoring, and collaboration between school and parents effectively reduce behavioral problems and improve students’ discipline and self-control. The study results can be applied in elementary education settings, character education programs, counseling services, and school management practices, providing practical guidance for teachers, counselors, administrators, and parents in developing preventive and corrective strategies for student behavioral issues while strengthening character education programs. The originality of this study lies in its integrated analysis combining psychological factors and religious character development strategies, demonstrating how spiritual habituation, empathetic guidance, and parental involvement collectively support behavioral improvement, thereby contributing new practical insights for advancing character education and student behavior management research in elementary school contexts.